2003
DOI: 10.1080/0963928032000091729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the validity of self-assessment: measuring computer literacy among entry-level undergraduates within accounting degree programmes at two UK universities

Abstract: This paper considers the validity of using self-assessment to measure computer literacy among entry-level undergraduate accounting students. Data collected from objective and self-appraisal computer literacy tests completed by students at two UK universities are analysed and the results of the tests compared for each student. The findings reveal significant differences in the students' perceived and actual computer literacy with the vast majority over-estimating their computer knowledge. Furthermore, evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…The use of self-assessment instruments of this type is not without problems. Indeed, criticising the self-ratings used in Stoner 1999, which are also used here, McCourt Larres et al (2003) conclude 'These findings indicate that self-assessment is not an appropriate means of determining computer literacy among entry-level undergraduate accounting students when used in isolation. ' (p. 97).…”
Section: Use Of Self-assessed Skills Ratingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of self-assessment instruments of this type is not without problems. Indeed, criticising the self-ratings used in Stoner 1999, which are also used here, McCourt Larres et al (2003) conclude 'These findings indicate that self-assessment is not an appropriate means of determining computer literacy among entry-level undergraduate accounting students when used in isolation. ' (p. 97).…”
Section: Use Of Self-assessed Skills Ratingsmentioning
confidence: 99%
“…Farh and Dobbins (1989) observe that access to comparative performance information improves subjects' self-assessments of their skills. McCourt Larres et al (2003), Mabe and West (1982) and van Vliet et al (1994) all report low or insignificant levels of self-leniency in specified circumstances, for example when the students are highly able. The students surveyed in this study are all of a high quality, based on their entrance qualifications, which provides some comfort that one of these conditions applies.…”
Section: Use Of Self-assessed Skills Ratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…McCourt Larres, Ballantine, and Whittington (2003) examined the validity of using student self-assessment in a within-subject experiment about computer literacy. At two schools, 381 entry-level accounting students completed a three-part research instrument before receiving any computer instruction.…”
Section: Other Skillsmentioning
confidence: 99%
“…A review of IT training needs and qualifications in a range of health‐care workers, with particular reference to the European Computer Driving Licence (ECDL), reported gains of approximately 40 minutes per day in staff time resulting from increased efficiency, and concluded that ECDL was a useful generic qualification (Stepankova & Engova, 2006). Mccourt Larres, Ballantine and Whittington (2003) compared objective testing with self‐evaluation of IT competence with cohorts of 1st‐year accounting students at the University of Warwick and the Queen's University of Belfast and found that there was no relationship between the two measures. They questioned the validity of self‐assessment and concluded that weak students overestimated whilst strong students underestimated their competence.…”
Section: Introductionmentioning
confidence: 99%